Geo-ekonomi: Dampak Terbentuknya Pakta Trilateral AUKUS terhadap ASEAN - Posma Sariguna Johnson Kennedy; Yudi Sutrasna; Haetami Haetami (Journal of Business and Economics Research (JBE), 2022)
Regional tensions strongly influence international economic and political relations in a strategic environment. The development of the current geo-economic view shows a mixture of economic and security interests that has begun to blur the separation. The emergence of the AUKUS trilateral pact consisting of Australia, Britain and the United States has further increased tensions in the Indo-Pacific region, especially with China. This study aims to examine the impact of AUKUS on ASEAN, in terms of the geo-economics that have changed at this time. This study was prepared using qualitative research methods through literature study. ASEAN centrality has not been able to face this challenge as a counterbalance so that each member country provides a variety of responses. The challenges ahead are much more difficult because the changing world order with the competition between America and China has shifted closer to their home, in the strategic Indo-Pacific region.